Clinical and radiological outcome after mechanical thrombectomy in acute ischemic stroke: What matters? - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Stefan; Dörfler, Arnd (Neuroradiology Journal, 2016)
Recent studies have shown the efficacy of mechanical thrombectomy in acute ischemic stroke. We sought to identify prognostic parameters for clinical and radiological outcome after mechanical thrombectomy.In 34 patients (age 72 ± 13 years, 64.7% women) with acute occlusion of the distal ICA and/or M1 segment who were treated with mechanical thrombectomy, the Spearman correlation was performed to assess potential prognostic outcome parameters (age, NIHSS, ASPECT, thrombus length (TL), clot burden score (CBS), relative filling time delay (rFTD), time to recanalization (TTR) and TICI score). The modified Rankin scale (mRS) and the Alberta Stroke Program Early CT (ASPECT) score were used for clinical and radiological outcome, respectively. Receiver operating characteristic (ROC) analysis was performed to assess parameters predicting favorable clinical (?mRS <= 2) and radiological outcome (?ASPECT <= 2).Variables associated with favorable clinical outcome included NIHSS, TL, TTR and TICI score (p <= 0.01) with NIHSS <= 15 (p = 0.001, area under the curve (AUC) 0.87), TL <= 2 cm (p = 0.017, AUC 0.75), TTR <= 231 min (p = 0.001 AUC 0.88) and TICI >= 2b (p = 0.050, AUC 0.70). Shorter TTR and higher TICI scores were associated with favorable radiological outcome (p < 0.001) with TTR <= 224 min (p = 0.023, AUC 0.77) and TICI >= 2b (p = 0.000, AUC 0.86).Fast and complete recanalization is essential to achieve a favorable radiological and functional outcome after mechanical thrombectomy in acute ischemic stroke. Age, CBS and collateral supply play a subordinate role.
EVALuna2:22544

Clot Burden and Collaterals in Anterior Circulation Stroke: Differences Between Single-Phase CTA and Multi-phase 4D-CTA - Kaschka, Iris; Kloska, Stephan; Struffert, Tobias; Engelhorn, Tobias; Gölitz, Philipp; Kurka, Natalia; Köhrmann, Martin; Schwab, Siegfried; Dörfler, Arnd (Clinical Neuroradiology, 2014)
It has been reported that the extent of intravascular thrombi and the quality of collateral filling in computed tomography (CT) angiography are predictive for the clinical outcome in patients with acute stroke. We hypothesized that multi-phase four-dimensional CTA (4D-CTA) allows better assessment of clot burden and collateral flow compared with arterial single-phase CTA (CTA).In 49 patients (33 female; age: 77 ± 12 years) with acute anterior circulation stroke, CTA and 4D-CTA reconstructed from dynamic perfusion CT data were analyzed for absolute thrombus length (TL), clot burden score (CBS), and collateral score (CS). The length of the filling defect was also defined on thin-slice nonenhanced CT as corresponding hyperdense middle cerebral artery sign (HMCAS) when present.There was good correlation (r = 0.62, p < 0.01) between the length of HMCAS (1.29 ± 0.62 cm) and TL in 4D-CTA (1.22 ± 0.51 cm). 4D-CTA and CTA significantly varied (p < 0.01) in TL (1.42 ± 0.73 cm (CTA) versus 1.11 ± 0.62 cm (4D-CTA)), CBS (median: 5, interquartile range: 4-7 (CTA) versus median: 6, interquartile range: 5-8 (4D-CTA); p < 0.001), and CS (median: 2, interquartile range: 1-2 (CTA) versus median: 3, interquartile range: 2-3 (4D-CTA); p < 0.001). Accordingly, CTA significantly overrated clot burden and underestimated collateral flow.4D-CTA more closely defines clot burden and collateral supply in anterior circulation stroke than CTA, implicating an additional diagnostic benefit.
EVALuna2:22276

Dabigatran Plasma Levels in Acute Cerebrovascular Events - Volbers, Bastian; Köhrmann, Martin; Kallmünzer, Bernd; Kurka, Natalia; Breuer, Lorenz; Ringwald, Juergen; Schwab, Stefan (Journal of Stroke and Cerebrovascular Diseases, 2016)
Oral anticoagulation with dabigatran was shown to be effective for stroke prevention in patients with nonvalvular atrial fibrillation without the need for laboratory monitoring. However, a recent publication based on data of the Randomized Evaluation of Long-Term Anticoagulation Therapy study reported that ischemic stroke and bleeding outcomes are correlated with dabigatran plasma concentration (DPC). DPC was determined at a prespecified time point and correlated with cardiovascular events at any time during follow-up. Because of the known variability of DPC, among others depending on renal function, this approach might compromise data evaluation. We report on dabigatran plasma levels in acute cerebrovascular events.Consecutive patients with acute ischemic stroke (AIS) or intracerebral hemorrhage (ICH) while taking dabigatran were retrospectively identified if admission DPC was available. DPC was determined using the diluted thrombin time (Hemoclot (HYPHEN BioMed, Neuville sur Oise, France)). Creatinine clearance (CrCl) was determined by measuring creatinine in plasma and 24-hour urine.Fifteen AIS and 4 ICH patients were included. Median DPC on admission was significantly higher in ICH patients than in AIS patients (135 ng/mL [interquartile range IQR 79-218] and 69.1 ng/mL [IQR 20.6-85.0], respectively; P = .035). Increased CrCl (values above published normal range) was correlated with lower median DPC (60 ng/mL [IQR 10-69] versus 100 ng/mL [IQR 79-157] in patients with normal CrCl, P = .01).Higher DPC was found in ICH patients than in AIS patients in temporal proximity to the event. Both decreased and increased renal functions seem to have an important influence on DPC.
EVALuna2:15996

Diagnostic value of prehospital ECG in acute stroke patients - Bobinger, Tobias; Kallmnzer, Bernd; Kopp, Markus; Kurka, Natalia; Heider, Stefan; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Neurology, 2017)
To investigate the diagnostic yield of prehospital ECG monitoring provided by emergency medical services in the case of suspected stroke.Consecutive patients with acute stroke admitted to our tertiary stroke center via emergency medical services and with available prehospital ECG were prospectively included during a 12-month study period. We assessed prehospital ECG recordings and compared the results to regular 12-lead ECG on admission and after continuous ECG monitoring at the stroke unit.Overall, 259 patients with prehospital ECG recording were included in the study (90.3% ischemic stroke, 9.7% intracerebral hemorrhage). Atrial fibrillation (AF) was detected in 25.1% of patients, second-degree or greater atrioventricular block in 5.4%, significant ST-segment elevation in 5.0%, and ventricular ectopy in 9.7%. In 18 patients, a diagnosis of new-onset AF with direct clinical consequences for the evaluation and secondary prevention of stroke was established by the prehospital recordings. In 2 patients, the AF episodes were limited to the prehospital period and were not detected by ECG on admission or during subsequent monitoring at the stroke unit. Of 126 patients (48.6%) with relevant abnormalities in the prehospital ECG, 16.7% received medical antiarrhythmic therapy during transport to the hospital, and 6.4% were transferred to a cardiology unit within the first 24 hours in the hospital.In a selected cohort of patients with stroke, the in-field recordings of the ECG detected a relevant rate of cardiac arrhythmia. The results can add to the in-hospital evaluation and should be considered in prehospital care of acute stroke.
EVALuna2:22506

Early Initiation of Anticoagulation with Direct Oral Anticoagulants in Patients after Transient Ischemic Attack or Ischemic Stroke - Macha, Kosmas; Volbers, Bastian; Bobinger, Tobias; Kurka, Natalia; Breuer, Lorenz; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin (Journal of Stroke and Cerebrovascular Diseases, 2016)
Direct oral anticoagulants (DOACs) are increasingly used for secondary prevention of cardioembolic stroke. While DOACs are associated with a long-term reduced risk of intracranial hemorrhage compared to vitamin K antagonists, pivotal trials avoided the very early period after stroke and few data exist on early initiation of DOAC therapy post stroke.We retrospectively analyzed data from our prospective database of all consecutive transient ischemic attack (TIA) or ischemic stroke patients with atrial fibrillation treated with DOACs during hospital stay. As per our institutional treatment algorithm for patients with cardioembolic ischemia DOACs are started immediately in TIA and minor stroke (group 1), within days 3-5 in patients with infarcts affecting one third or less of the middle cerebral artery, the anterior cerebral artery, or the posterior cerebral artery territories (group 2) as well as in infratentorial stroke (group 3) and after 1-2 weeks in patients with large infarcts (> 1/3 MCA territory, group 4). We investigated baseline characteristics, time to initiation of DOAC therapy after symptom onset, and hemorrhagic complications.In 243 included patients, administration of DOAC was initiated 40.5 hours (interquartile range [IQR] 23.0-65.5) after stroke onset in group 1 (n = 41) and after 76.7 hours (IQR 48.0-134.0), 108.4 hours (IQR 67.3-176.4), and 161.8 hours (IQR 153.9-593.8) in groups 2-4 (n = 170, 28, and 4), respectively. Two cases of asymptomatic intracranial hemorrhage (.8%) and 1 case of symptomatic intracranial hemorrhage (.4%) were observed, both in group 2.No severe safety issues were observed in early initiation of DOACs for secondary prevention after acute stroke in our in-patient cohort.
EVALuna2:22461

Impact of heart rate dynamics on mortality in the early phase after ischemic stroke: a prospective observational trial - Kallmünzer, Bernd; Bobinger, Tobias; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Journal of Stroke and Cerebrovascular Diseases, 2015)
Growing evidence suggests that the heart rate (HR) at rest is an independent predictor of cardiovascular mortality. In ischemic stroke, continuous monitoring of HR is the standard of care, but systematic data on its dynamics and prognostic value during the acute phase are limited.In this prospective observational study, HR was measured by continuous electrocardiographic monitoring on admission and during the first 72 hours of care among patients who were awake with ischemic stroke and survived until discharge. Functional outcome was assessed after 90 days.Data from 702 consecutive patients were analyzed (median age, 73 years, 54% men). The time course of HR was initially characterized by a rapid decline during the first 12 hours after admission. Among patients who survived until day 90, this was followed by a continuous downward trend in HR, whereas death after discharge was associated with a secondary increase and a reversal point 12 hours after admission. After adjustment for established risk factors, this secondary increase during the acute period was an independent predictor of death (hazard ratio, 3.73; 95% confidence interval, 1.47-9.43; P = .005).A secondary rise of HR during care for acute ischemic stroke is an early sign of fatality and may represent a surrogate for an unfavorable sympathetic disinhibition. Further research is warranted to clarify the role of targeted HR reduction after ischemic stroke (http://clinicaltrials.gov/, unique identifier NCT01858779).
EVALuna2:12023

Limited versus Whole-Brain Perfusion for the Indication of Thrombolysis in the Extended Time Window of Acute Cerebral Ischemia - Breuer, Lorenz; Knott, Michael; Struffert, Tobias; Kloska, Stephan; Kurka, Natalia; Schwab, Stefan; Dörfler, Arnd; Köhrmann, Martin; Engelhorn, Tobias (Journal of Stroke and Cerebrovascular Diseases, 2015)
Perfusion computed tomography (PCT) has emerged as alternative to magnetic resonance imaging (MRI) for assessment of patients clinically qualifying for off-label thrombolysis within 4.5 to 9 hours after onset of ischemic stroke. However, disadvantage of PCT is its often limited anatomic coverage with only 2 or 3 slices when using a 4- to 64-section scanner. Our purpose was therefore to evaluate the value of 2- and 3-slice perfusion compared to whole-brain perfusion.One hundred twenty-five patients undergoing MRI beyond 4.5 hours after symptom onset with supratentorial perfusion deficit were selected retrospectively. Accordingly to PCT slice positioning, 2 or 3 slices of the whole-brain perfusion weighted imaging data set were depicted. Volumes of infarct (using cerebral blood volume) and penumbra (using time-to-peak and cerebral blood volume) were calculated, and results were compared with 2- and 3-slice-derived volumes, respectively.Whole-brain imaging revealed a mismatch of more than 20% in 68.8% of patients (defined as 100%). Two-slice imaging detected a perfusion deficit in 72% and a mismatch in 48.8% (sensitivity = 70.9%). Three-slice imaging detected a perfusion deficit in 76% and a mismatch in 50.4% (sensitivity = 73.3%). Although there was no significant difference between 2- and 3-slice imaging (P > .23), both techniques revealed significantly less patients with mismatch compared to whole-brain coverage (P < .01).Two- and 3-slice imaging like obtained with PCT on most installed CT systems to assess perfusion deficits with subsequent mismatch calculation in acute stroke outside the 4.5-hour time window is significantly inferior to whole-brain coverage and, hence, has to be considered as a less-than-ideal solution.
EVALuna2:22358

Peripheral pulse measurement after ischemic stroke: A feasibility study - Kallmünzer, Bernd; Bobinger, Tobias; Kahl, Nicolas; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Marquardt, Lars; Schwab, Stefan; Köhrmann, Martin (Neurology, 2014)
To investigate feasibility and diagnostic accuracy of measurement of the peripheral pulse (MPP) at the radial artery as a simple, noninvasive screening tool for paroxysmal atrial fibrillation (pAF) in patients after acute ischemic stroke.Two hundred fifty-six patients with acute ischemic stroke and the patients' relatives at a tertiary stroke center were prospectively included. Participants were instructed for characteristics of atrial fibrillation (AF) in MPP using standardized educational material. Measurements of participants as well as a health care professional were then compared with simultaneous blinded ECG to evaluate diagnostic accuracy parameters.MPP by the health care professional or patients' relatives had a diagnostic sensitivity of 96.5% and 76.5%, respectively, with 94.0% and 92.9% specificity for the detection of AF. Self-measurements were reliably performed by 89.1% of competent patients with a diagnostic sensitivity of 54.1% and 96.2% specificity. False-positive results were limited to 6 cases (2.7%) with a positive predictive value of 76.9% and a negative predictive value of 90.0%.With a low rate of false-positive results, MPP offers an easy, ubiquitously available, noninvasive, first-step screening tool to guide ECG diagnostics for pAF after ischemic stroke. The data warrant a prospective trial evaluating the efficacy of MPP-guided ECG diagnostics in secondary prevention after stroke, which is now underway.This study provides Class I evidence that MPP by patients or relatives accurately distinguishes AF from normal heart rhythm as compared with continuous ECG.
EVALuna2:22299

Prevalence and impact on outcome of electrocardiographic early repolarization patterns among stroke patients: a prospective observational study - Bobinger, Tobias; Kallmünzer, Bernd; Kopp, Markus; Kurka, Natalia; Hilz, Max-Josef; Huttner, Hagen; Schwab, Stefan; Köhrmann, Martin; Arnold, Martin (Clinical Research in Cardiology, 2015)
Early repolarization pattern (ER) gained attention as a risk factor for ventricular arrhythmia and sudden cardiac death in the general population. While electrocardiographic abnormalities are frequent findings in stroke patients, data on ER pattern in this population are lacking.We assessed the prevalence of ER pattern in consecutive acute stroke patients at a tertiary stroke center. Functional outcome after 90 days was analyzed to determine the effect of an ER pattern on mortality. Multivariate logistic regression analysis was used to identify factors associated with an ER pattern.Out of 1141 consecutive stroke patients 771 patients remained for analysis after application of exclusion criteria. ER was observed in 62 (8.04%) patients. ER was more prevalent among subjects with intracerebral and subarachnoidal hemorrhage (13.0%) than among patients with ischemic stroke (7.0%; p = 0.024). Multiple regression analysis revealed QRS-duration (OR 0.972 95% CI 0.950-0.994, p = 0.012), QT-duration (OR 1.009, 95% CI 1.004-1.014, p = 0.001) and mechanical ventilation on admission (OR 0.320, 95% CI 0.136-0.752, p = 0.009) as independent predictors for ER. Overall ER on admission was not associated with increased mortality at 3-month follow-up (ER 11.3% vs. non-ER 9.2%; p = 0.582).ER is frequently found among patients with acute cerebrovascular events and is more prevalent in patients with hemorrhagic compared to ischemic events. Our study yields no evidence that ER is associated with worse outcome or mortality after stroke.
EVALuna2:12024

Reliability and limitations of automated arrhythmia detection in telemetric monitoring after stroke - Kurka, Natalia; Bobinger, Tobias; Kallmünzer, Bernd; Koehn, Julia; Schellinger, Peter D.; Schwab, Stefan; Köhrmann, Martin (Stroke, 2015)
Guidelines recommend continuous ECG monitoring in patients with cerebrovascular events. Studies on intensive care units (ICU) demonstrated high sensitivity but high rates of false alarms of monitoring systems resulting in desensitization of medical personnel potentially endangering patient safety. Data on patients with acute stroke are lacking.One-hundred fifty-one consecutive patients with acute cerebrovascular events were prospectively included. Automatically identified arrhythmia events were analyzed by manual ECG analysis. Muting of alarms was registered. Sensitivity was evaluated by beat-to-beat analysis of the entire recorded ECG data in a subset of patients. Ethics approval was obtained by University of Erlangen-Nuremberg.A total of 4809.5 hours of ECG registration and 22 509 alarms were analyzed. The automated detection algorithm missed no events but the overall rate of false alarms was 27.4%. Only 0.6% of all alarms indicated acute life-threatening events and 91.4% of these alarms were incorrect. Transient muting of acoustic alarms was observed in 20.5% patients.Continuous ECG monitoring using automated arrhythmia detection is highly sensitive in acute stroke. However, high rates of false alarms and alarms without direct therapeutic consequence cause desensitization of personnel. Therefore, acoustic alarms may be limited to life-threatening events but standardized manual evaluation of all alarms should complement automated systems to identify clinically relevant arrhythmias.
EVALuna2:22266

Repeated Intravenous Thrombolysis for Early Recurrent Stroke: Challenging the Exclusion Criterion - Kahles, Timo; Mono, Marie-Luise; Heldner, Mirjam Rachel; Baumgartner, Ralf Werner; Sarikaya, Hakan; Luft, Andreas; Bohlhalter, Stephan; Traenka, Christopher; Engelter, Stefan T.; Kurka, Natalia; Kohrmann, Martin; Curtze, Sami; et al. (Stroke, 2016)
Intravenous thrombolysis (IVT) within 4.5 hours from symptom onset improves functional outcome in patients with acute ischemic stroke. Its use in patients with previous stroke within the preceding 3 months is contraindicated because of the assumed higher risk of intracranial hemorrhage. In addition, tissue-type plasminogen activator may itself promote neurotoxicity and blood-brain barrier disruption. However, safety and effectiveness of repeated IVT is essentially unknown in patients with early (<3 months) recurrent stroke (ERS), because they were excluded from thrombolysis trials. This article reports the largest case series of repeated IVT in ERS.We reviewed databases of prospectively collected patient data of 8 European stroke centers for the presence of patients with ERS, who received IVT for both the index stroke and ERS. Demographics, clinical and radiological data, bleeding complications, and functional outcome were analyzed.We identified 19 subjects with repeated IVT in ERS. Mean age was 68±12 years, and 37% of them were female. Median interthrombolysis interval was 30 days (interquartile range, 13-50). Functional independence (modified Rankin scale score <=2) was achieved in 79% of patients after the first and in 47.4% after repeated IV tissue-type plasminogen activator, respectively. There was no symptomatic intracranial hemorrhage. Median final infarct volume after the first IVT was 1.5 cm(3) (interquartile range, 0.5-3.1).Patients with small infarct volumes and robust clinical improvement might be considered for repeated IVT within 3 months. Studies following strict protocols and larger registries incorporating these patients might serve to identify selection criteria for the safe use of repeated IVT in ERS.
EVALuna2:22476